THE EFFECTIVENESS OF TEPID WATER SPONGE (TWS) THERAPHY ON REDUCING POST -IMMUNIZATION INFANT BODY TEMPERATURE IN MAREDAN SIAK VILLAGE - Yanti; Jois Natalia Sinaga; Yan Sartika; Syafrisar Meri Agritubella (LLDIKTI Wilayah X, 2023)
Immunization is one way to provide immunity to various diseases but can cause side effects such as fever. Fever symptoms cause fussy children and increase parental concern. One effort that can be done is through compresses with warm water. The Purpose of this study was to determine the effect of Tepid Water Sponge on Reducing the baby’s body temperature after immunization. This type of Quantitative research with a quasi eksperiment design through a two group pretest post test control group design approach. The study population was 2-11 month-old baby who had post immunization fever with a sample of 30 people from February to March 2022 in Marendan Village, Siak. Sampling through purposive sampling technique. The research instrument uses an observation sheet. The statistical test used the Mann Whitney test with the results showing that the average decrease in the baby’s body temperature after the intervention was 0.8oC and 0,2oC in the control group. The conclusion is that there is a effect of the Tepid Water Spong on decreasing the baby’s body temperature after immunization (p value=0,000). Recommendations for giving this therapy can be done by parents independently at home when the baby has a fever.